Antisuicidal and antidepressant effects of ketamine and esketamine in patients with baseline suicidality: A systematic review. (May 2021) - Siegel, Ashley N.; Di Vincenzo, Joshua D.; Brietzke, Elisa; Gill, Hartej; Rodrigues, Nelson B.; Lui, Leanna M.W.; Teopiz, Kayla M.; Ng, Jason; Ho, Roger; McIntyre, Roger S.; Rosenblat, Joshua D.
Abstract: Suicide accounts for approximately 800, 000 deaths per year globally. Previous research has shown that intranasal esketamine and intravenous ketamine can rapidly decrease the severity of depressive symptoms and suicidal ideation. However, the majority of clinical trials excluded individuals with moderate to high baseline suicidality scores (e.g., suicidal ideation with plan/intent at the time of recruitment). The current review aims to evaluate the effect of esketamine and ketamine in patients with suicidal ideation at baseline. A systematic search was conducted on EMBASE, PsychInfo and PubMed from inception to July 2020 following the PRISMA guidelines. 15 studies met inclusion criteria. Results from esketamine trials did not demonstrate antisuicidal effects, as between-group differences were not found. Intravenous ketamine appeared to rapidly decrease the severity of suicidal ideation and depressive symptoms in individuals with baseline suicidal ideation, though retrospective studies suggest that these effects may be short-lasting. During the double-blind treatment phases, 2.4% of patients from the treatment groups and 1.5% of patients from control groups attempted suicide, with zero deaths by suicide in both the treatment and control groups during this phase. Based on the overall pooled samples, studies were assessed to be relatively safe, and the continual inclusion of this study population in future clinical trials is encouraged. Future research should aim to assess the longitudinal efficacy of ketamine in patients with baseline suicidality. Highlights: IV ketamine is associated with rapid & robust decreases in suicidal ideations. Esketamine has antidepressant effects in patients with baseline suicidality. The proportion of suicide attempts and death by suicide during these trials was low. Future trials should consider including patients with baseline suicidality.